Pseudo-Understanding in Mathematics: The Role of Habits of Mind and Gender Differences - Arifin, Sujinal; Susanti, Ely (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
This study explores the role of habits of mind and gender differences in shaping students' mathematical understanding, focusing on pseudo-understanding. Using a mixed-methods approach with a sequential explanatory design, the study involved 57 first-semester students of the Mathematics Education program at one of the public universities in Indonesia. Data were collected through mathematical concept comprehension tests, questionnaires on habits of mind, and semi-structured interviews. Three mathematics education experts validated the research instruments prior to their use. Quantitative data analysis was carried out descriptively to identify patterns of relationships among conceptual understanding, thought habits, and gender differences, while qualitative data were analyzed using a thematic approach. The results show that mind habits such as perseverance, cognitive flexibility, and reflection are essential in reducing pseudo-comprehension. Gender differences affect how students interact with mathematics, where stereotypes can hinder the development of strong habits of mind. This research highlights the importance of a pedagogical approach that emphasizes conceptual understanding and creates an inclusive classroom environment to diminish the risks of pseudo-understanding and gender disparities in mathematics learning.